The lethal disease of coconut in Ghana : developing markers and pathogen quantification techniques for the breeding of resistant or tolerant varieties - Yankey, Egya Ndede (2012)
Lethal diseases (LD) of coconut caused by phytoplasmas have destroyed millions of palms globally and pose a serious threat to the coconut industry in Ghana. This study investigated the genetic basis of resistance/tolerance of coconut varieties and hybrids to LD. The study was also aimed at developing molecular markers for cultivar verification to be used for the sustainable breeding of high value varieties and hybrids. Using PCR diagnosis and monitoring of symptoms of LD over a three year period, the study determined that escapee palms of the West African Tall ecotype (WAT) found in LD-devastated fields die once infected and do not represent resistant/tolerant sub-populations. Six monthly observations of symptoms and PCR diagnosis showed that LD-infection and symptom development occurred all year round. Quantification of phytoplasma amounts using novel quantitative real-time PCR methods did not reveal a pattern in pathogen disease titres between the rainy and dry seasons or between plant parts. Due to a lack of LD-infection in the sampled SGDxVrT and MYDxVrT palms, the basis of their resistance/tolerance could not be determined. Out of 44 microsatellites markers assessed for their usefulness in differentiating between the Ghanaian breeding materials, only two of the markers, CnCirC12 and CAC65 initially appeared to be associated with alleles specific for the susceptible 'West Africa Tall' variety but screening with further samples showed these two markers also to not be specific. The study found that palms of each variety did not show consistent genotypes for variety-specific SSR markers to be identified. Diagnostic assays based on the LAMP technique (DNA amplification at a single temperature using Bst polymerase) were assessed for their potential for in-field use. The simplicity of the technique and the rapidity with which results are obtained <30 min) demonstrated that this non-PCR technique could be a future method of choice for field diagnostics in Ghana and in Africa at large. Seeds from LD-infected palms were assessed for their ability to transmit the LD phytoplasma to progeny plants. Out of 105 coconut seedlings derived from LD-infected palms, none was found to be infected or developed LD after six monthly PCR diagnosis for 18 months. This study concludes that LD is unlikely to be seed transmitted and that the DNA fragments detected in coconut embryos may not represent a viable organism